탄성파 간섭법 탐사를 이용한 건축물 손상 평가 및 모니터링 - 정인석; In Seok Joung; 조아현; Ahyun Cho; 남명진; Myung Jin Nam (지구물리와 물리탐사, 2024)
최근 탄성파를 기반으로 건축물 안전진단(structure health monitoring, SHM)을 수행하는 방법들에 대한 연구들이 많이 수행되고 있다. 특히 지구물리탐사에서 주로 적용되어 오던 배경 잡음을 이용하는 탄성파 간섭법(seismic interferometry)이 SHM에 많이 적용되고 있다. 탄성파가 건축물 내부로 전파하며 발생하는 건축물의 반응을 분석하여 건축물의 강성 변화를 추정할 수 있을 뿐만 아니라, 건축물의 손상 여부와 그 위치도 평가할 수 있다. SHM에 적용되는 탄성파 간섭법에 대해 분석한 뒤 실제 적용 사례들도 분석한 결과, 탄성파 간섭법은 건축물의 안정성 평가나 모니터링 등에 적용할 수 있는 건축물 손상 탐지 평가 방법으로써 매우 효과적으로 활용할 수 있다고 판단된다. Recent research is increasingly focused on utilizing seismic waves for structure health monitoring (SHM). Specifically, seismic interferometry, a technique applied in geophysical surveys using ambient noise, is widely applied in SHM. This method involves analyzing the response of buildings to propagating seismic waves. This enables the estimation of changes in structural stiffness and the evaluation of the location and presence of damage. Analysis of seismic interferometry applied to SHM, along with case studies, indicates its highly effective application for assessing structural stability and monitoring building conditions. Seismic interferometry is thus recognized as an efficient approach for evaluating building integrity and damage detection in SHM and monitoring applications.